Tasa de degradación de madera por el perforador de manglar Psiloteredo healdi (Bivalvia:Teredinidae) en el Lago de Maracaibo, Venezuela - Rojas, José E; Severeyn, Héctor (Revista de Biología Tropical, 2000)
The degradation rate of wood substrates by the two species of bivalve molluscan bOfers, Ballkia fimbriatula and Psiloteredo healdi was studied in the mangrove forest of Ana María Campos Peninsula (Lake of Maracaibo, Venezuela). Pine wood substrates were placed in adjacent waters and the rate of infestatíon and growth (wood consumption) was recorded. The second species was dominant and occurred throughout the entire study (april lO october, 1 993), but rates of larval invasion and growth of individuals were influenced by the size of the population present P. healdi is capable of consuming as much 17 .Ix 1 0-3 g of woodlday